On the Relationship of expected supply and demand to futures prices - Hans Walter Chua; William G. Tomek (Cornell University, Charles H. Dyson School of Applied Economics and Management, 2010)
Expectations about future economic conditions are important determinants of commodity prices. This paper presents a relatively simple model that makes futures prices for corn a function of expected production and inventories and of variables that account for demand shifts. The intent is to provide an historical, objective context for new price and quantity observations, which may help market analysts.
Keywords: 330; expected supply; futures prices; commodity prices